The frontrunner - Kilduff, Paul (Hodder & Stoughton, 2001)
The Chinese premier's assasination triggers a global financial crisis. The Central Bankers decide to turn this into profitable recovery by enlisting Jonathan Maynard's help. But as the markets turn he wonders who will share these gains - and why did five Bankers make him an offer he can't refuse?